Public health ethics: towards a research agenda - Thompson, Alison; Robertson, Ann; Upshur, Ross (Acta Bioethica, 2003)
Public health ethics, as distinct from clinical/medical bioethics, is an emerging field of study in academic settings. As part of a larger effort to address what the conceptual and content boundaries of this field are, or ought to be, a group at the University of Toronto hosted an international working symposium to discuss and outline a research agenda for public health ethics. The symposium, which took place in May 2002, was organized into four major areas of ethical concern central to public health: individual rights and the common good; risk and precaution; surveillance and regulation; and social justice and global health equity. This paper will provide an overview of some of the main themes and issues that emerged from the key papers that were developed from the symposium and discuss their importance in the emerging field of public health ethics. Significant issues were identified, such as the importance of distinguishing public health ethics from traditional bioethics; the development of the notion of common interests; broad definitions of public health, that include upstream sources of health inequities, and an understanding of the theoretical landscape from which public health ethics has emerged.